Natural resources, urbanisation, economic growth and the ecological footprint in South Africa: The moderating role of human capital - Nathaniel, Solomon Prince (Quaestiones Geographicae, 2021)
South Africa is the largest emitter of CO2 and arguably the most developed and urbanised country in Africa. The country currently harbours an ecological deficit territory which could be the outcome of economic expansion, urban explosion, unsustainable resource exploration and a low level of human development. After all, environmental distortions are mainly the outcome of human activities. This study is a maiden attempt to examine the linkage between urbanisation, human capital, natural resources (NR) and the ecological footprint (EF) in South Africa. Unlike previous studies, this study employs positivist and relevant environmental indicators that accommodate built-up land, forest land, carbon footprint, ocean, grazing land and cropland. Findings from the long-run results suggest that urbanisation, economic growth and NR increase the EF, whereas human capital ensures environmental sustainability. The interaction between urbanisation and human capital mitigates environmental degradation by reducing the EF. The canonical cointegrating regression (CCR), dynamic ordinary least squares (DOLS) and the fully modified ordinary least squares (FMOLS) results further confirm the nature of the relationships and linkages existing with respect to NR, urbanisation, economic growth and the EF. A bidirectional causality exists between human capital, economic growth and the EF. Policies related to NR and urban sustainability, the limitations of the study, as well as possible directions for future research are discussed.